Pengaruh Model Pembelajaran Inkuiri Terhadap Hasil Belajar Matematika Materi Pecahan Senilai Siswa Kelas IV SD Negeri Dampit - Paramitha, Aghfanny Prajna; Wahyuni, Holy Ichda; Setiawan, Fajar Ichda (Widyagogik, 2025)
This study aims to discuss the implementation of project-based cooperative learning in inclusive elementary school classrooms by utilizing environmental space as a learning resource. The study employs a descriptive qualitative method with data collection techniques including observation, interviews, and documentation to provide an in-depth description of how this learning strategy is applied, the interaction between regular students and students with special needs, as well as how the school environment is utilized to support learning. The findings show that the implementation of project-based cooperative learning can enhance collaboration between regular students and students with special needs, as well as the use of the environmental space as a learning resource, enriching the students' experiences and engagement. The implications of this study highlight the importance of integrating cooperative learning with the utilization of the environment as a learning resource in the context of inclusive classrooms, which can improve the quality of learning and students' social skills. Project-based cooperative learning using environmental space has been proven effective in supporting inclusive education, where appropriate data collection techniques provide a deeper understanding of the learning process and outcomes.